Milnacipran: serotonin-noradrenaline reuptake inhibitor approved for fibromyalgia may be a useful antidepressant. (October 2018) - Keks, Nicholas A; Hope, Judy; Keogh, Simone; Copolov, David L
Objective: Milnacipran is a serotonin noradrenaline reuptake inhibitor (SNRI) approved for treatment of fibromyalgia in Australia, but is used for depression in Europe and elsewhere. This paper will briefly review milnacipran and its utility in psychiatry for the treatment of depression. Conclusion: Milnacipran is a dual reuptake inhibitor of noradrenaline and serotonin, with greater effect on noradrenaline than serotonin, in contrast to the related drugs venlafaxine, desvenlafaxine and duloxetine. Rapidly absorbed irrespective of food, milnacipran has a half-life of approximately 8 hours, reaches steady state in 2 days and is excreted renally. Milnacipran helps a minority of patients with fibromyalgia by reducing pain and fatigue. It is also an effective antidepressant with efficacy comparable to venlafaxine and duloxetine, and a side effect profile characteristic of SNRIs. The dose range is 50–200 mg, in divided doses. Milnacipran may be useful for patients with depression and pain, and endogenous depression characterised by anergia, psychomotor retardation and hypersomnia. Caution is necessary in the presence of heart disease, hypertension, renal impairment, epilepsy, glaucoma, bipolar disorder, and bleeding tendency. Milnacipran is likely to be a useful late antidepressant option in treatment-resistant patients, as well as those with chronic pain, anergia and hypersomnia.